An Examination of the Structure of Sustainable Facilities Planning Scale for User Satisfaction in Nigerian Universities (Construction Economics and Building, 2014)
Universities are under increasing pressure to demonstrate that continuous performance improvement is being delivered for user satisfaction, but the importance of facilities planning as a student-staff focused tool needs to be emphasised. This research sought answers to questions relating to the underlying structure of sustainable facilities planning and user satisfaction, and the number of factors that make up the facilities planning scale. Three universities from the south-western part of Nigeria were selected randomly using ownership structure to define the cases: University of Lagos, Akoka, Lagos, Ladoke Akintola University of Technology, Ogbomoso and Joseph Ayo Babalola University, Ikeji Arakeji, each representing the Federal, State, and Private ownership. A questionnaire survey was used on a random sample of 651 staff and students from the three universities. Six hundred questionnaires were retrieved (response rate of 92.2%). An exploratory factor analysis was used to understand the responses and the interrelationships. The results showed a two-factor solution of ‘locational advantages and user needs’ and ‘adequacy of facilities/functional connection and four core determinants for acceptance. It is concluded that universities should factor student-staff focus points into their facilities planning schemes to optimise their service deliveries. The study contributes to the discussion on factor structure of sustainable facilities planning scale with a focus on students and staff of universities. Keywords: Facilities planning, universities, data structure, factors, Nigeria.